145. Analysis of dose deposition in lung lesions: A more robust optimization based on a modified PTV. (December 2018) - Monti, A.F.; Brito, D.A.; Brambilla, M.G.; Carbonini, C.; Ferrari, M.B.; Zanni, D.; Mainardi, H.S.; Torresin, A.
Abstract : Purpose: SBRT in lung delivers high doses to a small dense nodule (GTV) moving into a low density tissue. If IMRT/VMAT is used, an apparently homogeneous dose is delivered, but high photon fluence is generated inside the PTV-GTV shell due to its low electron density (ED). So the GTV, moving into PTV, will receive a dose depending on its position. Methods: A TPS "Monaco" (MC algorithm) was used to simulate a dummy patient (55 Gy in 5 fractions). In step1, in order to consider the motion of the high ED GTV, the photon fluence was optimized for the original PTV ED (EDo) and thus used to calculate the dose on a "forced" PTV ED (EDf), in which the ED of the PTV was forced to the mean ED of the GTV. In step2, the photon fluence was optimized for PTV EDf and then used for dose calculation on PTV EDo to evaluate the dose variation on the lower ED region of the PTV and inside the GTV. Comparisons between the original and recalculated dose were made accordingly: dose profiles, Dmean, D98% and D2% for PTV-GTV. Results: In step1 dose profiles differ up to 6.6%, 3.4% and 3.8% on longitudinal, sagittal and transversal axes along the isocenter. Increments of 1.6% for D98%, 2.5% for Dmean and 5% for D2% were obtained for PTV-GTV (see Fig. 1 In step2 differences between dose profiles were −3% for all. A reductions of −1.5% for D98%, −1.5% for Dmean and −1.4% for D2% were achieved for PTV-GTV. Conclusions: Step1 shows that the dose to GTV is higher than what estimated on the original EDo map. The GTV is irradiated in a more homogeneous way in step2. Optimizing the photon fluence for the "forced" density map appears an effective way to evaluate the real GTV dose.